Can Markets Secure Economic and Social Human Rights - Branco, Manuel (2015)
In recent years, state inefficiency in delivering some public goods to everyone has been the major argument set forth by those who argue that markets should play a more active role in providing those goods and services that are needed to secure human rights. In result, in many parts of the world, we have been witnessing a privatization of social security and water distribution, for example. This article argues that markets do not speak the same language as human rights and therefore are not fully prepared to play the role of a supplier of goods and services as human rights, and specifically of the rights to social security and to water. There are three essential reasons for that. First markets do not state social preferences, second they are not accountable and finally they are inefficient. In essence, markets commodify human rights and while filling them with exchange value they empty them of political significance.